Is Work Associated With More or Less Criminal Involvement in the Short-Term? New Evidence of the Former Among a Justice-Involved Sample? - Bellair, Paul E. (Crime & delinquency, 2024)
We inquire whether commitment to employment has an immediate suppressive effect (i.e., in the next month) on street crime. Analysis of retrospective monthly calendar data drawn from a random sample of prisoners reveals that it does not. In contrast, paycheck work co-occurs with income generating crime in almost half of the months in which participants are employed. Second, paycheck work is associated with an increase in the likelihood of subsequent drug selling and bears no association with violent or property offenses. Third, job commitment is associated with greater odds of drug selling. Finally, hours worked does exert an immediate suppressive effect on drug selling and violent crime, but the effects are relatively small and do not challenge our main conclusions.